Healthcare in the United States Navigating the Basics of a Complex System - Howe, Deanna L.; Dozier, Andrea L.; Dickenson, Sheree O. (Open textbook library., 2022)
This book is a collaborative effort among three faculty members from the Darton College of Health Professions, Nursing Department, at Albany State University, a Historically Black College and University (HBCU), and part of the UniversitySystem of Georgia. The book idea originated from a grant-funded program to create open education resources (OER) for students learning in UniversitySystem of Georgia’s eMajor courses. The cost of education in the United States is remarkably expensive, and the added burden of purchasing textbooks for each course can be prohibitive. The opportunity to create free educational materials has been a rewarding experience. A free pdf form of this text is available for download. The authors of this book are registered nurses who have each worked 25 or more years in various roles and specialties within our healthcare system. There have been many changes throughout the years. The authors’ experience and knowledge are from a nursing perspective not found in other texts of similar content.The healthcare system has advanced tremendously since the very beginning of our formalized system. The most significant growth has been in technology use to support, diagnose, increase patient safety, and document patient outcomes.However, more can be done to ensure a system that meets all our citizens’ healthcare needs.Readers of this text will learn a brief history of our healthcare system and explore the current state of health in the U.S. In the next 12 chapters, readers will: consider health as defined using determinants of health discover the many types of healthcare providers seen throughout the system differentiate between the different types of healthcare settings explore state and federal programs that provide oversight examine private insurance and managed care plans survey access issues and the cost of healthcare review how state and federal government provides support to special populations discover the quick expansion of technology use in healthcare assess quality determinants and accreditation standards compare national healthcare systems presently used to the present U.S.healthcare system identify advantages of a national healthcare system for the UnitedStates This book will describe and explain our current healthcare system’s complexities by providing the basics of many components in easy to understand terminology. Each chapter includes essential features to assist the student in learning and understanding.